Preparation method and application of sodium ion battery hard carbon negative electrode material

By mixing the biomass precursor with lignite, heat treatment and carbonization, high-performance hard carbon anode material is prepared, which solves the problems of poor electrochemical performance and high production cost of existing sodium ion battery anode materials, and realizes the efficient preparation and commercial application of sodium ion batteries.

CN119706792APending Publication Date: 2025-03-28UNIV OF SCI & TECH LIAONING
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411898482.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing sodium ion battery anode materials show poor electrochemical performance in sodium ion batteries and have high production costs, which hinders the commercialization of sodium ion batteries.

Method used

By mixing the biomass precursor with lignite, heat treatment and carbonization treatment, a hard carbon negative electrode material with high first-term efficiency, good cycle performance, small specific surface area and high and low potential platform capacity were prepared.

Benefits of technology

The high-performance preparation of hard carbon anode materials for sodium ion batteries is achieved, which reduces production costs and improves the availability of materials, and promotes the commercial application of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706792A_ABST
    Figure CN119706792A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a sodium ion battery hard carbon negative electrode material. The preparation method comprises the following steps: 1) drying, crushing and grinding a biomass precursor; 2) placing the ball-milled lignite in a mixed solution of hydrochloric acid and hydrofluoric acid, stirring, performing vacuum filtration, cleaning with deionized water, and drying to obtain lignite powder; and 3) mixing the two powders, performing heat treatment, performing heat treatment in a tubular furnace, cooling, washing in 1mol / L hydrochloric acid, performing suction filtration, and drying. The method has the advantages that the lignite and the common biomass precursor are compounded for electrochemical energy storage, and the prepared hard carbon material has the characteristics of high first efficiency, better cycle performance, smaller specific surface area, high and low potential platform area capacity and the like. Besides, the lignite is used as one part of the raw material, so that the production cost of the material can be reduced, the compaction density and the tap density of the composite material can be increased, and the availability of biomass carbon is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries and relates to a preparation method and application of a hard carbon negative electrode material for a sodium ion battery. Background Art

[0002] The excessive use of fossil fuels is the main cause of the greenhouse effect, leading to frequent extreme weather events around the world. Therefore, the development of sustainable renewable energy is of great practical significance. Lithium-ion batteries (LIBs) dominate the global electrochemical power source market with their high energy density, long cycle life and high rate performance. However, due to the shortage of lithium resources and high cost, lithium-ion batteries cannot fully meet the needs of large-scale electrochemical energy storage systems. Sodium-ion batteries have the advantages of low cost and abundant resources, and are considered to be a promising commercial battery to replace lithium-ion batteries for EES systems.

[0003] However, the radius of sodium ions is much larger than that of lithium ions. Therefore, the graphite negative electrode that has been commercialized in lithium-ion batteries shows poor electrochemical performance in sodium-ion batteries, with a reversible capacity of only 31 mAh / g. At present, the main challenge facing sodium-ion batteries is to design suitable sodium storage materials. Compared with the large number of studies on positive electrode materials in recent years, the research on negative electrode materials is slightly lagging behind, which has hindered the commercialization of sodium-ion batteries. Among the many negative electrode materials for sodium-ion batteries, carbon-based materials are considered to be the most promising negative electrode materials for sodium-ion batteries for commercial application due to their excellent sodium storage performance, good stability, low cost, green environmental protection and renewability.

[0004] Hard carbon has been widely studied as anode material for sodium ion batteries due to its low redox potential, stable structure and unique disordered structure. Thanks to the large interlayer distance and lattice defects of hard carbon, it exhibits high reversible capacity in sodium ion batteries. However, the precursors used to produce hard carbon, such as biomass, resin, organic polymer, etc., usually show low carbon yield and poor rate performance, which is not conducive to the low cost advantage of sodium ion batteries and reduces the competitiveness of sodium ion batteries in various energy storage technologies. The precursors for preparing soft carbon materials mainly include petrochemical raw materials and their downstream products, such as coal, asphalt, petroleum coke, etc., but directly carbonized soft carbon materials show low reversible capacity in sodium ion batteries.

[0005] Therefore, if high-performance carbon negative electrode materials can be successfully prepared using low-cost soft carbon as a precursor, it will further promote the development of sodium-ion batteries. Therefore, it is hoped that a hard carbon negative electrode with high first efficiency and high and low potential platform capacity will be developed, and more simple and environmentally friendly manufacturing processes will be developed to mass-produce asphalt-derived carbon to promote and realize the commercial application of asphalt-derived carbon materials in sodium-ion batteries. Microcrystalline hybrid enhanced coal-based carbon negative electrode for advanced sodium-ion batteries (Chen He, Sun Ning, Zhu Qizhen, et al., Journal of Advanced Science, 2022, 7(20): 202200023), by introducing a hard carbon precursor (sucrose) into lignite, the composite material prepared by direct pyrolysis has a large proportion of pseudo-graphite structure. The sodium storage capacity of lignite was increased from 290mAh / g to 356mAh / g by reacting with O3-NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 assembled a sodium-ion full battery with an energy density of up to 240Wh / kg. It can be seen that microcrystal regulation of soft and hard carbon composites is a feasible strategy to improve sodium storage performance. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a hard carbon negative electrode material for a sodium ion battery and its application. The hard carbon material obtained by the preparation method has high initial efficiency, good cycle performance, small specific surface area and high and low potential platform capacity.

[0007] To achieve the above object, the present invention is implemented through the following technical solutions:

[0008] A method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps:

[0009] 1) Place the biomass precursor in a drying oven, dry at 60-120°C for more than 24 hours, and crush and grind to less than 200 mesh;

[0010] 2) The ball-milled lignite is placed in a mixed solution of hydrochloric acid and hydrofluoric acid, stirred at 60-80° C. for 24-36 hours to remove minerals in the lignite, and then vacuum filtered, washed with deionized water and dried to obtain lignite powder;

[0011] 3) the powder obtained in step 1) and the black lignite powder obtained in step 2) are uniformly mixed in a mass ratio of 1:1 to 1:5;

[0012] 4) heat treating the mixed powder obtained in step 3) at 300-500° C. in an air atmosphere for 0.5-2 h to obtain a hard carbon precursor;

[0013] 5) The hard carbon precursor is loaded into a magnetic boat and then placed in a tube furnace, and heat treated at 1100-1400° C. for 0.5-5 h in an inert atmosphere, and a black solid is obtained after cooling;

[0014] 6) The black solid was washed in 1 mol / L hydrochloric acid, filtered and dried to obtain a hard carbon negative electrode material for a sodium ion battery.

[0015] The volume ratio of hydrochloric acid to hydrofluoric acid in the mixed solution is 1:1 to 1:3.

[0016] The powder obtained in step 1) in step 3) is 1.0-2.0 g, and the black lignite powder obtained in step 2) is 1.0-2.0 g.

[0017] The biomass precursor is selected from one or more of eggplant, loofah and radish.

[0018] The heat treatment in step 4) is to increase the temperature to 300-500° C. at a heating rate of 5-10° C. / min and keep the temperature for 0.5-2 h.

[0019] In step 5), the temperature is increased to 1100-1400° C. at a heating rate of 1-5° C. / min in a tube furnace.

[0020] The inert atmosphere in step 5) is a nitrogen atmosphere or an argon atmosphere.

[0021] An application of a sodium ion battery hard carbon negative electrode material, wherein the prepared sodium ion battery hard carbon negative electrode material is used as the main material of the sodium ion battery negative electrode plate.

[0022] The sodium ion battery negative electrode plate is prepared by mixing a sodium ion battery hard carbon negative electrode material, a conductive agent and a binder in a mass ratio of 90:(1-5):(1-5).

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention uses lignite and common biomass precursors to composite for electrochemical energy storage. The hard carbon material prepared has the characteristics of high initial efficiency, good cycle performance, small specific surface area, and high and low potential platform capacity compared with other sodium ion carbonaceous negative electrode materials. In addition, using lignite as part of the raw material can not only reduce the production cost of the material, but also increase the compaction density and tap density of the composite material, greatly improving the availability of biomass carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a flow chart for the preparation of lignite and biomass composite materials.

[0026] Figure 2 This is the XRD diagram of the lignite and eggplant carbon composite material in Example 1.

[0027] Figure 3This is the SEM image of the lignite and eggplant carbon composite material in Example 1.

[0028] Figure 4 This is the FT-IR image of the lignite and eggplant carbon composite material in Example 1.

[0029] Figure 5 This is a rate performance diagram of the lignite and eggplant carbon composite material used in Example 1 as a negative electrode material for a sodium ion battery.

[0030] Figure 6 This is a charge and discharge curve diagram of the lignite and eggplant carbon composite material used as a negative electrode material for a sodium ion battery in Example 1.

[0031] Figure 7 This is a cycle performance diagram of the lignite and eggplant carbon composite material in Example 1 applied to the negative electrode material of a sodium ion battery after 1000 cycles at 1 A / g.

[0032] Figure 8 This is the XRD diagram of the lignite and loofah carbon composite material in Example 2.

[0033] Fig. 9 This is a cycle performance diagram of the lignite and loofah carbon composite material in Example 2 applied to the negative electrode material of a sodium ion battery after 1000 cycles at 1 A / g.

[0034] Fig.10 This is the XRD diagram of the lignite and radish carbon composite material in Example 3.

[0035] Fig.11 This is a cycle performance diagram of the lignite and radish carbon composite material in Example 3 applied to the negative electrode material of a sodium ion battery after 1000 cycles at 1 A / g. DETAILED DESCRIPTION

[0036] The present invention is described in detail below in conjunction with the accompanying drawings, but it should be noted that the implementation of the present invention is not limited to the following embodiments.

[0037] See Figure 1 , a method for preparing a hard carbon negative electrode material for a sodium ion battery, comprising the following steps:

[0038] 1) Place the biomass precursor in a drying oven, dry at 60-120° C. for more than 24 hours, and crush and grind to less than 200 meshes. The biomass precursor is selected from one or more of eggplant, loofah, and radish.

[0039] 2) The ball-milled lignite (100-200 mesh) is placed in a mixed solution of hydrochloric acid and hydrofluoric acid, stirred at 60-80° C. for 24-36 hours to remove minerals in the lignite, and then vacuum filtered, washed with deionized water and dried to obtain lignite powder; the volume ratio of hydrochloric acid to hydrofluoric acid in the mixed solution is 1:1-1:3.

[0040] 3) The powder obtained in step 1) and the black lignite powder obtained in step 2) are uniformly mixed in a mass ratio of 1:1 to 1:5; preferably, the powder obtained in step 1) is 1.0 to 2.0 g, and the black lignite powder obtained in step 2) is 1.0 to 2.0 g.

[0041] 4) The mixed powder obtained in step 3) is heat treated at 300-500° C. in an air atmosphere for 0.5-2 h to obtain a hard carbon precursor; the heat treatment is performed by heating the temperature to 300-500° C. at a heating rate of 5-10° C. / min and keeping the temperature for 0.5-2 h.

[0042] 5) The hard carbon precursor is placed in a magnetic boat and then placed in a tube furnace, and heat treated at 1100-1400° C. for 0.5-5 h in an inert atmosphere, and a black solid is obtained after cooling; the temperature is increased to 1100-1400° C. in the tube furnace at a heating rate of 1-5° C. / min. The inert atmosphere is a nitrogen atmosphere or an argon atmosphere.

[0043] 6) The black solid was washed in 1 mol / L hydrochloric acid, filtered and dried to obtain a hard carbon negative electrode material for a sodium ion battery.

[0044] An application of a sodium ion battery hard carbon negative electrode material, wherein the prepared sodium ion battery hard carbon negative electrode material is used as the main material of a sodium ion battery negative electrode plate. The sodium ion battery negative electrode plate is made by mixing the sodium ion battery hard carbon negative electrode material, a conductive agent (SP), and a binder (CMC) in a mass ratio of 90:5:5.

[0045] Example 1

[0046] See Figure 1 , a method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps:

[0047] 1) Place the eggplant in a drying oven at 80°C and dry for 24 hours. Remove excess moisture and then crush and grind to less than 200 mesh for later use.

[0048] 2) The ball-milled lignite (100-200 mesh) was placed in a mixed solution of hydrofluoric acid and hydrochloric acid (1:2) and stirred at 60°C for 24 hours to remove minerals in the lignite, and then the lignite powder was collected by vacuum filtration, deionized water washing and drying.

[0049] 3) 1.0 g of the powder obtained in step 1) was mixed with 2.0 g of the black powder obtained in step 2) to obtain a brown powder.

[0050] 4) The brown powder obtained in step 3) is cross-linked and carbonized in an air atmosphere at 400° C. with a heating rate of 5° C. / min and heat treated for 2 h to obtain the product.

[0051] 5) The black powder obtained in step 4) is loaded into a magnetic boat and placed in a tube furnace. An inert gas, preferably argon, is introduced and heat treated at 1400° C. for 2 h to allow the hard carbon precursor to undergo a cross-linking reaction.

[0052] 6) The black solid obtained in step 5) is washed in 1 mol / L hydrochloric acid, filtered and dried to obtain the final product, lignite / eggplant composite material.

[0053] See Figure 2 The lignite / eggplant carbon composite sample has two obvious diffraction peaks near 24° and 43°, corresponding to the (002) characteristic peak and (100) characteristic peak of carbon, respectively. From the XRD spectrum, it can be obtained that the d 002 =0.378nm.

[0054] See Figure 3 , SEM test of lignite / eggplant carbon composite material shows obvious flaky structure. This flaky structure is conducive to the diffusion of electrolyte, accelerates the diffusion rate of sodium ions, and is conducive to the storage of sodium ions, thereby improving the rate performance and cycle performance of electrode materials.

[0055] See Figure 4 FT-IR test of lignite and eggplant carbon composite material As can be seen from the figure, the infrared spectrum shows that the carbon material has -OH (~3433cm -1 ), -COOH(~1250cm -1 ), -CO(~1116cm -1 ) and -C=O (~1708cm -1 ) and other oxygen-containing functional groups.

[0056] See Figure 5 When the lignite and eggplant carbon composite material was used as the negative electrode of sodium ion battery, after 10 cycles at different current densities of 30mA / g, 50mA / g, 100mA / g, 200mA / g, 500mA / g and 1000mA / g, the discharge specific capacity was 305.6mAh / g, 303.7mAh / g, 299.8mAh / g, 290.37mAh / g, 275.7mAh / g and 258.7mAh / g respectively. It can be seen that it has good rate performance at high current density.

[0057] Depend on Figure 6It can be seen that at a current density of 30mA / g, its first coulombic efficiency is 92.59%. In addition, the capacity of the slope area above 0.1V of the half-cell comes from the adsorption of sodium ions by the surface defects of the carbon material. The platform area below 0.1V corresponds to the intercalation reaction of sodium ions, and the platform capacity is 198.5mAh / g. The conversion of the graphite-like structure, which accounts for a large proportion, to the pseudo-graphite structure gives the material a higher platform capacity.

[0058] Depend on Figure 7 It can be seen that at a current density of 1 A / g, the capacity retention rate after 1000 cycles is 88.12%, which shows that the prepared hard carbon negative electrode material for sodium ion batteries has good structural stability.

[0059] Example 2

[0060] See Figure 1 , a method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps:

[0061] 1) Dry the loofah in a drying oven at 80°C for 24 hours, remove excess moisture, and then crush and grind to less than 200 mesh for later use.

[0062] 2) The ball-milled lignite (100-200 mesh) was placed in a mixed solution of hydrochloric acid and hydrofluoric acid (volume ratio 1:2) and stirred at 60°C for 24 hours to remove minerals in the lignite, and then the lignite powder was collected by vacuum filtration, deionized water washing and drying;

[0063] 3) 1.0 g of the powder obtained in step 1) and 3.0 g of the black powder obtained in step 2) were mixed evenly to obtain a brown powder;

[0064] 4) The brown powder obtained in step 3) is cross-linked and carbonized in an air atmosphere at 400° C. with a heating rate of 5° C. / min and heat treated for 2 h to obtain a hard carbon precursor.

[0065] 5) The black powder obtained in step 4) is loaded into a magnetic boat and placed in a tube furnace. An inert gas, preferably argon, is introduced and heat treated at 1400° C. for 2 h to allow the hard carbon precursor to undergo a cross-linking reaction. After cooling, a black solid is obtained.

[0066] 6) The black solid obtained in step 5) is washed in 1 mol / L hydrochloric acid, filtered and dried to obtain the final product, lignite / loofah composite material.

[0067] See Figure 8 , the lignite / luffa carbon composite material sample has two obvious diffraction peaks near 24° and 43°, corresponding to the (002) characteristic peak and (100) characteristic peak of carbon, respectively. From the XRD spectrum, it can be obtained that the d 002 =0.376nm.

[0068] Depend on Fig. 9 It can be seen that when the lignite / loofah carbon composite material is used for the negative electrode of the sodium ion battery, the capacity retention rate is 89.55% after 1000 cycles under the conditions of a current density of 1A / g and a voltage range of 0.01V to 3V.

[0069] Example 3

[0070] See Figure 1 , a method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps:

[0071] 1) Dry the radish in a drying oven at 80°C for 24 hours, remove excess moisture, and then crush and grind to less than 200 mesh for later use.

[0072] 2) The ball-milled lignite (100-200 mesh) was placed in a mixed solution of hydrochloric acid and hydrofluoric acid (volume ratio 1:2) and stirred at 60°C for 24 hours to remove minerals in the lignite, and then the lignite powder was collected by vacuum filtration, deionized water washing and drying;

[0073] 3) 1.0 g of the powder obtained in step 1) was mixed evenly with 1.0 g of the black powder obtained in step 2) to obtain a brown powder.

[0074] 4) The brown powder obtained in step 3) was heated to 400° C. at a heating rate of 5° C. / min in an air atmosphere and heat treated for 2 hours to obtain a hard carbon precursor.

[0075] 5) The black powder obtained in step 4) is placed in a magnetic boat and placed in a tube furnace, and an inert gas, preferably argon, is introduced, and heat treated at 1400° C. for 2 hours to cause a cross-linking reaction of the hard carbon precursor, and a black solid is obtained after cooling;

[0076] 6) The black solid obtained in step 5) is washed in 1 mol / L hydrochloric acid, filtered and dried to obtain the final product, lignite / radish composite material.

[0077] Fig.10 XRD test of lignite / radish carbon composite material shows that the lignite / radish carbon composite material sample has two obvious diffraction peaks near 24° and 43°, corresponding to the (002) characteristic peak and (100) characteristic peak of carbon, respectively. From the XRD spectrum, it can be obtained that the d 002 =0.39nm.

[0078] Depend on Fig.11 It can be seen that when the lignite / radish carbon composite material is used for the negative electrode of the sodium ion battery, the capacity retention rate is 86.65% after 1000 cycles under the conditions of a current density of 1A / g and a voltage range of 0.01V to 3V.

[0079] The present invention uses lignite as a precursor, mixes the dried and ground biomass precursor and lignite evenly in an agate mortar, pre-carbonizes at low temperature in an air atmosphere, and then carbonizes at 1100-1400°C to cause a cross-linking reaction in the hard carbon precursor; the carbonized sample is washed with hydrochloric acid, the pH is adjusted to neutral, and dried to obtain a carbon material, which is then prepared into an electrode sheet for a sodium ion negative electrode material. The preparation method of the present invention is simple and is conducive to the large-scale preparation of the product; the electrochemical energy storage using lignite and biomass carbon materials is combined, showing excellent performance such as high initial efficiency, good cycle performance, small specific surface area, and high and low potential platform area capacity.

Claims

1. A method for preparing a hard carbon negative electrode material for a sodium ion battery, characterized in that: The following steps are involved: 1) Place the biomass precursor in a drying oven, dry at 60-120°C for more than 24 hours, and crush and grind to less than 200 mesh; 2) The ball-milled lignite is placed in a mixed solution of hydrochloric acid and hydrofluoric acid, stirred at 60-80° C. for 24-36 hours to remove minerals in the lignite, and then vacuum filtered, washed with deionized water and dried to obtain lignite powder; 3) the powder obtained in step 1) and the black lignite powder obtained in step 2) are uniformly mixed in a mass ratio of 1:1 to 1:5; 4) heat treating the mixed powder obtained in step 3) at 300-500° C. in an air atmosphere for 0.5-2 h to obtain a hard carbon precursor; 5) The hard carbon precursor is loaded into a magnetic boat and then placed in a tube furnace, and heat treated at 1100-1400° C. for 0.5-5 h in an inert atmosphere, and a black solid is obtained after cooling; 6) The black solid was washed in 1 mol / L hydrochloric acid, filtered and dried to obtain a hard carbon negative electrode material for a sodium ion battery.

2. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: The volume ratio of hydrochloric acid to hydrofluoric acid in the mixed solution is 1:1 to 1:

3.

3. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: The biomass precursor is selected from one or more of eggplant, loofah and radish.

4. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: The heat treatment in step 4) is to increase the temperature to 300-500° C. at a heating rate of 5-10° C. / min and keep the temperature for 0.5-2 h.

5. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step 5), the temperature is increased to 1100-1400° C. at a heating rate of 1-5° C. / min in a tube furnace.

6. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: The inert atmosphere in step 5) is a nitrogen atmosphere or an argon atmosphere.

7. An application of the hard carbon negative electrode material for sodium ion batteries prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The prepared sodium ion battery hard carbon negative electrode material is used as the main material of the sodium ion battery negative electrode plate.

8. The use of a hard carbon negative electrode material for sodium ion batteries according to claim 7, characterized in that: The sodium ion battery negative electrode plate is prepared by mixing a sodium ion battery hard carbon negative electrode material, a conductive agent and a binder in a mass ratio of 90:(1-5):(1-5).

Citation Information

Patent Citations

  • Preparation method of coal-based hard carbon negative electrode material as well as product and application of coal-based hard carbon negative electrode material

    CN117945385A